Personal Reflections on the Matriculture of the Siberian Soviet Union: Transcript - Shalamova, Nadya (Matrix, 2026)
In this recorded interview, Dr. Nadya Shalamova shares her personal reflections about being a women in Siberia during the Soviet period and about Siberian Soviet matriculture. Transcript available (see PDF).LINK TO VIDEO INTERVIEW: Personal Reflections on the Matriculture of the Siberian Soviet Union.